New trends in modern education - М. А. Tlevtsezheva (Вестник Майкопского государственного технологического университета, 2024)
The restructuring of higher education should be considered as one of the urgent, most important tasks of accelerating the social and economic development of the state and modern personnel policy. Universities are called upon to have a long-term, ever-increasing impact on the accelerated movement of society, dynamic transformation of the economy, improvement of social relations, and radical restructuring of all aspects of life. Universities have a special role in the development of the humanization of the society and the spiritual culture of the people; for this it is necessary to ensure a transition to the training of general specialists based on a combination of fundamental, general scientific, general professional knowledge and areas of practical training, individually differentiating the content and terms of training for specialists with higher education depending on the nature of their future professional activities – design, technological, technical, engineering, management, research and other possible ones. It is necessary to strengthen the interdisciplinary connections of the disciplines studied, adapting the graduate to the needs of the market, moving on to training specialists with a training period of five to six years. No other sector of the economy has undergone such dramatic changes in such a short period. In this article the author made an attempt to conduct a retrospective analysis of the higher education system in the Russian Federation, highlighting existing problems and outlining possible development prospects.